2014
DOI: 10.3174/ajnr.a3877
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Inflow Zone of Unruptured Cerebral Aneurysms: Comparison of 4D Flow MRI and 3D TOF MRA Data

Abstract: BACKGROUND AND PURPOSE:The hemodynamics of the inflow zone of cerebral aneurysms may be a key factor in coil compaction and recanalization after endovascular coil embolization. We performed 4D flow MR imaging in conjunction with 3D TOF MRA and compared their ability to identify the inflow zone of unruptured cerebral aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…In addition, 4D flow MR imaging may have the limitation of spatial resolution. 15,22 These disadvantages can cause unstable and irregular streamline patterns irrelevant to the vascular shape on 4D flow MR images. High-resolution MR imaging at Ͼ3T may decrease these artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, 4D flow MR imaging may have the limitation of spatial resolution. 15,22 These disadvantages can cause unstable and irregular streamline patterns irrelevant to the vascular shape on 4D flow MR images. High-resolution MR imaging at Ͼ3T may decrease these artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…32 Using 4D flow MR imaging, we recently reported that the inflow zone was not located on the distal neck in 25% of sidewall aneurysms. 15 In this study, we defined the locations of the inflow zones more precisely by investigating the correlation between inflow zone location and parent artery central axis on the en face image of the section plane of the aneurysm orifice by using 4D flow MR imaging. Consequently, the inflow zone was located on the distal neck in 31.3%, the lateral side of the neck in 59.4%, and the proximal neck in 9.4% of unruptured sidewall ICA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the clinical applications of DSA are limited (9). MRA possesses a number of advantages, including non-invasiveness, no requirement for radiation, a high distinguishing capacity in soft tissues and the possibility of multiparameter comparison and imaging (10). 3D-TOF MRA is the most common angiography technology in clinical practice, and the primary advantage of 3D-TOF MRA is the acquisition of a wide range of cerebral artery MRA images in a relatively short period.…”
Section: Discussionmentioning
confidence: 99%